Network-based risk assessment of ship-mediated dispersal of non-native species across Chilean and international ports - Javier Pinochet; Reinaldo Rivera; Antonio Brante (Scientific Reports)
Abstract Marine biological invasions threaten global biodiversity, making it essential to identify high-risk areas for effective management and prevention. This study assesses the risk of non-native species (NNS) dispersal through maritime transport using network analysis to examine connectivity patterns among Chilean and international ports, complemented by an environmental similarity approach for estimation. The results highlight San Antonio, San Vicente, and Concepción Bay as key nodes within the national network, facilitating maritime traffic redistribution and linking the Central Chile and Araucanian ecoregions, identified as critical corridors for NNS introduction and spread. In contrast, secondary ports such as Corral and Mejillones have limited connectivity and play minor roles in the network. Internationally, Chilean ports maintain frequent connections with global hubs such as Panama and Shanghai, emphasizing their role in global maritime traffic. Procrustes analysis reveals strong environmental similarity between connected regions, suggesting that shared conditions enhance NNS survival and establishment. Alluvial diagrams and network illustrate high-risk routes and port, aiding in the identification of critical areas for monitoring and management. This study underscores the importance of integrating network analysis with environmental data as a key tool for assessing invasion risk, prioritizing strategic areas, and strengthening preventive strategies.